The impact of community closures among nonessential and essential workers, Nashville, Tennessee: A cross‐sectional study. Issue 3 (24th May 2022) - Rankin, Danielle A.; Yanis, Ahmad; Haddadin, Zaid; Talj, Rana; Fernandez, Kailee N.; Bloos, Sean M.; Stahl, Anna; Gu, Wenying; Nicotera, Janet; Howe, Harrison L.; Salib, Seifein; Chappell, James; et al.
Abstract: Background and Aims: The effects of community closures and relaxing social distancing restrictions on severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) by occupational risk remain unclear. Therefore, we evaluated the impact of community closures and reopening phases with the prevalence of testing SARS‐CoV‐2‐positive among nonessential and essential workers. Methods: We constructed a cross‐sectional cohort from March 20 to July 31, 2020, of 344 adults from Metropolitan Nashville, Tennessee. We performed an unconditional logistic regression model to evaluate the impact of community closures and phase implementation on testing SARS‐CoV‐2 positive by occupation to estimate adjusted prevalence odds ratios (aPORs) and 95% confidence intervals (CIs). Results: During a stay‐at‐home/Phase I order, those with non‐essential occupations had 59% decreased prevalence odds (aPOR:0.41; 95% CI: 0.20–0.84) of testing SARS‐CoV‐2‐positive compared to when no restrictions were in place. Persons with essential occupations had four times the prevalence odds of testing SARS‐CoV‐2‐positive (aPOR:4.19; 95% CI:1.57–11.18) compared with nonessential occupations when no community restrictions were established. Conclusion: Stay‐at‐home restrictions were associated with a lower risk of SARS‐CoV‐2 infection in the community for nonessential workers. Essential employees remained at increased risk for SARS‐CoV‐2, including when no community restrictions were in place and vaccines were not available. This study supports targeting prevention measures for these high‐risk occupations.